2020
DOI: 10.3390/ijms21165700
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into the Anti-Inflammatory Effects of the Curcumin Ester Prodrug Curcumin Diglutaric Acid In Vitro and In Vivo

Abstract: Curcumin diglutaric acid (CurDG), an ester prodrug of curcumin, has the potential to be developed as an anti-inflammatory agent due to its improved solubility and stability. In this study, the anti-inflammatory effects of CurDG were evaluated. The effects of CurDG on inflammatory mediators were evaluated in LPS-stimulated RAW 264.7 macrophage cells. CurDG reduced the increased levels of NO, IL-6, and TNF- α, as well as iNOS and COX-2 expression in cells to a greater extent than those of curcumin, along with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Several studies showed that the prodrug and formulation development of drugs and bioactive compounds could improve bioavailability and biological activities [ 39 , 40 , 41 , 58 ]. A previous study showed that the phospholipid complex of quercetin could improve the solubility of quercetin and enhance the protective effect against oxidative-induced damages in ARPE-19 cells compared to quercetin [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that the prodrug and formulation development of drugs and bioactive compounds could improve bioavailability and biological activities [ 39 , 40 , 41 , 58 ]. A previous study showed that the phospholipid complex of quercetin could improve the solubility of quercetin and enhance the protective effect against oxidative-induced damages in ARPE-19 cells compared to quercetin [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prodrug approach has been shown to enhance pharmacological properties by improving physico-chemical and biopharmaceutical properties such as aqueous solubility, stability, bioavailability and biological activities [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. We have previously demonstrated that curcumin digluatric acid, an ester prodrug of curcumin conjugated with diglutaric acid, improved the biological activities of curcumin both in vitro and in vivo [ 41 , 42 ], suggesting that glutaric acid could serve as a promoiety of bioactive molecules. The conjugation of Lut with diglutaric acid via an ester bond can possibly increase the pharmacological and biological activities of Lut.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin exerts various pharmacological activities, including antioxidant, anticancer, anti-inflammatory, and anti-infective. Curcumin affects various signaling molecules associated with the inflammatory processes, such as TNF-α, IL-1β, NF-κB, COX-2, and iNOS [165,166]. Curcumin was observed to regulate the differentiation of naïve CD4+T cells and activate IL-10 immune modulation against acute lung injury in mice and thus alleviated lung injury and suppressed uncontrolled inflammation [167].…”
Section: Extended Polyphenolic Compoundsmentioning
confidence: 99%
“…Inflammation, considered as one of the principal responses of the immune system, involves redness, swelling, pain, heat, and dysfunction [10]. Non-steroidal anti-inflammatory drugs are used to treat inflammation.…”
Section: Introductionmentioning
confidence: 99%